1995
DOI: 10.1016/s0266-7681(05)80099-3
|View full text |Cite
|
Sign up to set email alerts
|

The Treatment of Chronic Flexion Contractures of the Proximal Interphalangeal Joint

Abstract: A method of treatment of chronic flexion contractures of the PIP joint is presented, with the results obtained in 19 patients treated between 1989 and 1992 after a follow-up of from 6 to 53 months. The flexion contractures, with an extension deficit which ranged between 70 and 90 degrees, had been present for a period of between 2 months and 24 years. Our treatment program involves the surgical release of the unreducible PIP joint followed by the use of static and/or dynamic splints. Surgery is performed using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
24
0
2

Year Published

2004
2004
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 7 publications
1
24
0
2
Order By: Relevance
“…Other investigators have used line drawings similar to his in reports on the stiff PIPJ. 7,12 The description by Bowers 2 was similar to the findings in this study but with some differences. Bowers 2 described the origin of the PCL as being located eccentrically in the concave area on the side of the condyles of the proximal phalanx.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Other investigators have used line drawings similar to his in reports on the stiff PIPJ. 7,12 The description by Bowers 2 was similar to the findings in this study but with some differences. Bowers 2 described the origin of the PCL as being located eccentrically in the concave area on the side of the condyles of the proximal phalanx.…”
Section: Discussionsupporting
confidence: 84%
“…In general the orientation of the PCL is shown as oblique and/or cord-like and narrow in its anteroposterior dimension. [3][4][5][6][7][8][9][10][11][12] Other investigators describe it as being a broader structure. 2 The ACL usually is shown as a substantial structure that is triangular in shape and to which stabilizing properties are ascribed.…”
mentioning
confidence: 99%
“…The concept of surgical correction of proximal interphalangeal joint contracture by release of the capsuloligamentous structures of the joint was described by Watson et al (1979) and subsequently addressed by other authors over the last 20 years (Abbiati et al, 1995;Diao and Eaton, 1993;Rajesh et al, 2000;Tonkin et al, 1985). Andrew (1991), in a cadaveric study, demonstrated not only that full correction of proximal interphalangeal joint contracture in Dupuytren's disease could be attained by surgical means but identified the accessory collateral ligaments and volar plate as the important structures involved.…”
Section: Introduction and Aimsmentioning
confidence: 99%
“…2,7,13,14 Clinically, adhesion of the VP is one of the important factors causing a flexion contracture of the PIP joint. 10,11,[15][16][17][18] Releasing contractures of the VP and its supporting structures is a treatment option for the contracture; however, it may still be difficult to obtain a satisfactory surgical outcome. [15][16][17][18] Although its importance is well recognized, there has been little investigation of the normal biomechanical behavior of the VP.…”
mentioning
confidence: 99%
“…10,11,[15][16][17][18] Releasing contractures of the VP and its supporting structures is a treatment option for the contracture; however, it may still be difficult to obtain a satisfactory surgical outcome. [15][16][17][18] Although its importance is well recognized, there has been little investigation of the normal biomechanical behavior of the VP. 1,5 We previously conducted a dynamic ultrasonographic study of the biomechanics of the VP 19 and showed that the normal VP motion was mainly composed of sliding, elevating, and rolling in the recess (Fig.…”
mentioning
confidence: 99%